Programa para la autorregulación del aprendizaje - Ramírez Castro, Alexandra; Peña Pérez, Eliana Gisel; Lesmes Lesmes, Adriana Marcela; Saavedra Velandia, Francy Lorena; López Ramírez, Kelly Johana; Hernández Romero, Gabriela; Chitiva Núñez, Naydw; Rodríguez, Diana Eugenia (Lee La LEE, 2023)
Programa para la autorregulación del aprendizaje